Hematochezia in children with acute diarrhea seeking emergency department care – a prospective cohort study. (8th February 2022) - Böhrer, Madeleine; Fitzpatrick, Eleanor; Hurley, Katrina; Xie, Jianling; Lee, Bonita E.; Pang, Xiao‐Li; Zhuo, Ran; Parsons, Brendon D.; Berenger, Byron M.; Chui, Linda; Tarr, Phillip I.; Ali, Samina; et al.
Abstract: Objectives: Although the passage of blood in stools in children represents a medical emergency, children seeking emergency department (ED) care remain poorly characterized. Our primary objective was to compare clinical characteristics and etiologic pathogens in children with acute diarrhea with and without caregiver‐reported hematochezia. Secondary objectives were to characterize interventions and resource utilization. Methods: We conducted a secondary analysis of the Alberta Provincial Pediatric EnTeric Infection TEam (APPETITE) database. Children <18 years presenting to two pediatric EDs within a 24‐hour period and <7 days of symptoms were consecutively recruited. Results: Of 1, 061 participants, 115 (10.8%) reported hematochezia at the enrollment visit at which time those with hematochezia, compared to those without, had more diarrheal episodes/24‐hour period (9 vs. 6; difference: 2; 95% confidence interval [CI]: 2.0, 4.0; p < 0.001), and were less likely to have experienced vomiting (54.8% vs. 80.2%; difference: −25.4; 95% CI: −34.9, −16.0; p < 0.001). They were more likely to receive intravenous fluids (33.0% vs. 17.9%; difference: 15.2; 95% CI: 6.2, 24.1; p < 0.001) and require repeat health care visits (45.5% vs. 34.7%; difference: 10.7; 95% CI: 0.9, 20.6; p = 0.03). A bacterial pathogen was identified in 33.0% of children with hematochezia versus 7.9% without (difference: 25.1; 95% CI: 16.3, 33.9; p < 0.001); viruses were detected in 31.3% of children with hematochezia compared to 72.3% in those without (difference: −41.0%, 95% CI: −49.9, −32.1; p < 0.001). Conclusion: In children with acute diarrhea, caregiver report of hematochezia, compared to the absence of hematochezia, was associated with more diarrheal but fewer vomiting episodes, and greater resource consumption. The former group of children was also more likely to have bacteria detected in their stool.